Constructing effective ion channels in anion exchange membranes via exfoliated nanosheets towards improved conductivity for alkaline fuel cells. Issue 12 (19th May 2022) - Sharma, Prem P.; Manohar, Murli; Kim, Dukjoon
Abstract : A series of quaternized polysulfone (QPS)-based composite membranes containing various amounts of functionalized graphitic carbon nitride (f-g-C3 N4 ) nanosheets were synthesized. Abstract : A series of quaternized polysulfone (QPS)-based composite membranes containing various amounts of functionalized graphitic carbon nitride (f-g-C3 N4 ) nanosheets were synthesized. The synergistic effects of the incorporated nanosheets were investigated on a variety of membrane properties for alkaline fuel cell application, such as hydroxyl ion conductivity, swelling ratio, water uptake, chemical stability, and cell performance. The well-interacting architecture of the f-g-C3 N4 nanosheets containing multiple hydrophilic sites was the main reason for the enhanced hydroxide ion conductivity of the membrane. The QPS–CN-5 membrane showed a high hydroxide ion conductivity of 16–37 mS cm −1 in a temperature range from room temperature to 80 °C because of the highly interlocked ionic domains of the porous tris-triazine units in the f-g-C3 N4 nanosheets. The single-cell test of QPS–CN-5 exhibited a maximum power density of 77 mW cm −2 .